Victims of dating violence in adolescence: the role of problematic use of social networks sites, loneliness, and family climate - Muñiz-Rivas, Maria; Suárez-Relinque, Cristian; Estévez, Estefanía; Povedano-Díaz, Amapola (Anales de Psicología / Annals of Psychology, 2023)
The relationship between online-offline socialization contexts during adolescence has become a relevant research topic in recent years, especially in the field of intimate partner violence. To better understand this association, the present study analyzes the relationship between dating violence (DV) victimization and the problematic social networking sites use (PSNSU), the feeling of loneliness, and the family climate, taking into account the adolescents' gender. 1020 adolescents from Andalusia participated (49% boys, M = 16.12, SD = .99). A cluster analysis, which established two groups (victimized and non-victimized), multivariate analysis of variance (2x2 MANOVA) using sex and DV as independent variables, and univariate analysis of variance to explore the significant relationships detected, were performed. The results showed that adolescent victims of DV obtained higher scores than non-victims in PSNSU, feelings of loneliness, and family conflict, and lower scores in family cohesion. Victimized girls generally showed lower scores than victimized boys. The results obtained provide relevant and useful information for the prevention of DV and the promotion of healthy relationships in early dating relationships. In addition, they point out the importance of considering the online context in research on violence in adolescence.